Upaya Guru Meningkatkan Karakter Kerja Sama Anak Usia Dini 5-6 Tahun Melalui Permainan Tradisional Bakiak di Kober Miftahul Huda - Ai Cucu Melar; Elnawati Elnawati; Redi Awal Maulana (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2025)
This research aims to improve the character of early childhood cooperation (5-6 years) through the application of traditional clogs in Kober Miftahul Huda. The character of cooperation is an important aspect in the social-emotional development of early childhood that needs to be instilled from an early age. This research uses the Classroom Action Research (PTK) approach which is carried out in two cycles. Each cycle consists of stages of planning, implementation, observation, and reflection. The subjects of the study were 15 children aged 5-6 years in Kober Miftahul Huda. Data were collected through observation, documentation, and interviews. Data analysis was carried out in a qualitative and quantitative descriptive manner. The results of the study showed an increase in the character of children's cooperation after the implementation of traditional clogs games. In the first cycle, the percentage of children's cooperation reached 65%, while in the second cycle it increased to 85%. Indicators of improved cooperation include children's ability to share tasks, help each other, and communicate effectively in groups. Thus, the traditional game of clogs has proven to be effective in improving the character of early childhood cooperation. It is recommended to educators to use traditional games as a learning medium that supports the development of children's social-emotional aspects.